Road connectivity, population, and crop production in Sub-Saharan Africa - Dorosh, Paul A.; Wang, Hyoung Gun; You, Liangzhi; Schmidt, Emily (Wiley, 2012)
This study adopts a cross‐sectional spatial approach to examine the relationship between transport infrastructure, population location, and agricultural production in Sub‐Saharan Africa using new data obtained from geographic information systems (GIS). We find that both population and agricultural production are spatially concentrated near large cities, with 41.4% of population and 23.6% of agricultural production (in value terms) within 2.5 hours travel time to large cities. Taking into account agroecological and other factors, we find a statistically significant association between travel time and agricultural production. Using coefficients estimated for Mozambique, we simulate the effects of hypothetical increases in road investments on travel times and agricultural production, suggesting that improvements in road infrastructure could facilitate a substantial increase in agricultural production.